2012
DOI: 10.2528/pier12022001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Clutter Suppression for Airborne Random Pulse Repetition Interval Radar Based on Compressed Sensing

Abstract: Abstract-We present an adaptive clutter suppression method for airborne random pulse repetition interval radar by using prior knowledge of clutter boundary in Doppler spectrum. In this method, by exploiting the intrinsic sparsity, compressed sensing based on iterative grid optimization (CS-IGO) is applied to directly recover the clutter spectrum with only the test range cell instead of nonhomogeneous training data from adjacent range cells. Since the sensing matrix and clutter spectrum obtained by CS-IGO are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Some of the research exists on the clutter suppression of airborne radar [25][26][27]. Similarly, some adaptive filter algorithms were used for clutter cancellation in PBR [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the research exists on the clutter suppression of airborne radar [25][26][27]. Similarly, some adaptive filter algorithms were used for clutter cancellation in PBR [22].…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of compressed sensing based methods have been applied to radar systems [8][9][10][11][12][13][14][15][16][17][18], which recover the target scene from fewer measurements than traditional methods. In [8], it is demonstrated that the compressed sensing can eliminate the need for matched filter at the receiver and has the potential to reduce the required sampling rate.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], it is demonstrated that the compressed sensing can eliminate the need for matched filter at the receiver and has the potential to reduce the required sampling rate. [9] presents an adaptive clutter suppression method for airborne random pulse repetition interval radar by using prior knowledge of clutter boundary in Doppler spectrum. [10] focuses on monostatic chaotic multiple-input-multiple-output (MIMO) radar systems and analyze theoretically and numerically the performance of sparsity-exploiting algorithms for the parameter estimation of targets at Low-SNR.…”
Section: Introductionmentioning
confidence: 99%
“…So far, CS theorem has been widely used in the signal processing of SAR [16][17][18][19][20]. Lin et al applied CS to CSAR imaging, aiming to reduce the number of samples and provide high image quality [21].…”
Section: Introductionmentioning
confidence: 99%